The Therapeutic Potential of Targeting Substance P/NK-1R Interactions in Inflammatory CNS Disorders - Johnson, M. Brittany; Young, Ada D.; Marriott, Ian (Frontiers in Cellular Neuroscience, 2017)
The inflammatory responses of resident central nervous system (CNS) cells are now known to play a critical role in the initiation and progression of an array of infectious and sterile neuroinflammatory disorders such as meningitis, encephalitis, Parkinson’s disease, Alzheimer’s disease and multiple sclerosis. Regulating glial inflammatory responses in a timely manner is therefore critical in preserving normal CNS functions. The neuropeptide substance P is produced at high levels within the CNS and its selective receptor, the neurokinin 1 receptor (NK-1R), is abundantly expressed by neurons and is present on glial cell types including microglia and astrocytes. In addition to its functions as a neurotransmitter in the perception of pain and its essential role in gut motility, this tachykinin is widely recognized to exacerbate inflammation at peripheral sites including the skin, gastrointestinal tract, and the lungs. Recently, a number of studies have identified a role for substance P and NK-1R interactions in neuroinflammation and described the ability of this neuropeptide to alter the immune functions of activated microglia and astrocytes. In this review, we describe the expression of substance P and its receptor by resident CNS cells, and we discuss the ability of this neuropeptide to exacerbate the inflammatory responses of glia and immune cells that are recruited to the brain during neurodegenerative diseases. In addition, we discuss the available data indicating that the NK-1R-mediated augmentation of such responses appears to be detrimental during microbial infection and some sterile neurodegenerative disorders, and propose the repurposed use of NK-1R antagonists, of a type that are currently approved as anti-emetic and anti-anxiolytic agents, as an adjunct therapy to ameliorate the inflammatory CNS damage in these conditions.